Analysis Of Decision Number 331/Pdt.G/2025/Pa.Bgr About The Impact Of Online Judi On Household Protection (Case Study Of Bogor Religious Court) - Nova Ramadanti,; Yono,; Ade irma Imamah, (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
The rise of online gambling in the digital era not only raises legal and moral concerns but also poses a serious threat to family resilience. This phenomenon often becomes a major trigger of household conflict, particularly when one partner is involved in gambling practices, leading to the neglect of economic responsibilities, emotional instability, and the breakdown of family relationships. This study aims to analyse Decision Number 331/Pdt.G/2025/PA. Bogor is a representative case of divorce caused by online gambling addiction. The research employs a descriptive qualitative approach using a case study method. Data were obtained through interviews with a judge at the Bogor Religious Court and document analysis of the court decision. The findings reveal that the husband’s involvement in online gambling directly disrupted the economic functions of the family, including neglect of financial support, the sale of household assets, and debt accumulation. Moreover, this addiction undermined family harmony, eroded trust, and diminished the well-being and future of the children, ultimately resulting in divorce. The factors that drive individuals into online gambling include easy access to information technology, economic instability, irregular employment, permissive social environments, and the desire to gain instant profits. These findings indicate that online gambling is a real threat to family resilience and requires serious attention from various parties through legal, social, and educational measures. Keywords: Online Gambling; Household Resilience; Court Decision